Long-Term Effects of Childhood Nutrition: Evidence from a School Lunch Reform - Jesper Alex-Petersen; Petter Lundborg; Dan-Olof Rooth (Institute of Labor Economics (IZA), 2017)
We examine the long-term impact of a policy that introduced free and nutritious school lunches in Swedish primary schools. For this purpose, we use historical data on the gradual implementation of the policy across municipalities and employ a difference-in-differences design to estimate the impact of this lunch policy on a broad range of medium and long-term outcomes, including lifetime income, health, cognitive skills, and education. Our results show that the school lunch program generated substantial long-term benefits, where pupils exposed to the program during their entire primary school period have 3 percent greater life-time earnings. In addition, we find the effect to be greater for pupils that were exposed at earlier ages and for pupils from poor households. Finally, exposure to the school lunch program had substantial effects on educational attainment and health and these effects can explain a large part of the return to school lunches.
Keywords: I12; I38; J24; 330; income; long-term; childhood; early life; nutrition; causal